Bibliometric analysis of recent research on multidrug and antibiotics resistance (2017–2018) - David Gómez-Ríos, Howard Ramírez-Malule (Journal of Applied Pharmaceutical Science, 2019)
Antibiotic resistance is considered, nowadays, as a severe public health problem. In February 2017, the World Health Organization (WHO) reported the global priority list of antibiotic-resistant bacteria as a guide for further research on the field. This contribution presents a bibliometric overview of global research on multidrug and antibiotics resistance. Research articles indexed between 2017 and 2018 on the Scopus database were filtered according to a systematic search strategy and a total of 2,362 records were retrieved. A significative number of studies were found to be focused on four pathogenic bacteria: Escherichia coli, Pseudomonas aeruginosa, Acinetobacter baumannii, and Klebsiella pneumoniae, which were also included in the critical priority level according to the WHO. The results of this study indicate that the United States, China, and India were the most productive countries regarding the number of publications. Furthermore, publications from the United States, Germany, and the United Kingdom had the highest impact based on the ratio of the number of citations and the number of publications. Nevertheless, when productivity was stratified by the number of publications and the number of citations based on the gross domestic product, Iran ranked first. This bibliometric approach showed that most of multidrug- and antibiotics-resistance studies focused on the so-called critical bacteria according to the WHO but less on those bacteria catalogued as high and medium priority.
Keywords: Antibiotics resistance, multidrug resistance, bibliometric analysis.